A Meta‐Analysis of the Government Performance—Trust Link: Taking Cultural and Methodological Factors into Account. - Zhang, Jiasheng; Li, Hui; Yang, Kaifeng (Public Administration Review, 2022)
The performance‐trust link constitutes an important issue, but the public administration and political science literature has been equivocal regarding how it is influenced by cultural and methodological factors. Meta‐analyzing 72 empirical studies, this article finds that the link is stronger in low power distance countries, when outputs are used to measure government performance, or when the focus is on local government. In addition, the performance‐trust link holds true regardless of whether performance data are subjective or objective, or whether the studies focus on performance of government as a whole or specific agencies. The results imply that in order to nurture and sustain trust in government, we should pay more attention to societal cultures and the way government performance information is provided. Trust in government studies should become both more scientific and more culturally sensitive.